2020
DOI: 10.3390/jcm9072279
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial 18F-FDG Uptake Pattern for Cardiovascular Risk Stratification in Patients Undergoing Oncologic PET/CT

Abstract: Objective: Positron emission tomography/computed tomography with 18F-fluorodeoxy-glucose (18F-FDG-PET/CT) has become the standard staging modality in various tumor entities. Cancer patients frequently receive cardio-toxic therapies. However, routine cardiovascular assessment in oncologic patients is not performed in current clinical practice. Accordingly, this study sought to assess whether myocardial 18F-FDG uptake patterns of patients undergoing oncologic PET/CT can be used for cardiovascular risk stratifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…As such, this task may slightly differ from regular heart segmentation on CT [ 35 , 36 ] or MR [ 37 , 38 ], but, also requires both CT and FDG-PET data. The uptake of FDG in the heart muscle of patients undergoing chemo-therapy has been investigated [ 39 ] and focal myocardial FDG uptake indicates a significant increased risk for multiple myocardial abnormalities. As such, this heart segmentation model could be used as an automated tool to assist the measurement of myocardial uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As such, this task may slightly differ from regular heart segmentation on CT [ 35 , 36 ] or MR [ 37 , 38 ], but, also requires both CT and FDG-PET data. The uptake of FDG in the heart muscle of patients undergoing chemo-therapy has been investigated [ 39 ] and focal myocardial FDG uptake indicates a significant increased risk for multiple myocardial abnormalities. As such, this heart segmentation model could be used as an automated tool to assist the measurement of myocardial uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As part of an oncologic PET protocol, patients were fasted to avoid myocardial 18 F-FDG uptake: 36% of patients had no 18 F-FDG uptake, 22.5% had diffuse 18 F-FDG uptake, 8% had focal 18 F-FDG uptake, and 30.5% had a focal uptake overlying the diffuse pattern 18 F-FDG uptake. Among all the patients, multivariate logistic regression identified focal myocardial 18 F-FDG uptake as a predictor of impaired LVEF and myocardial perfusion (131). It is important to bear in mind two interesting points.…”
Section: Nuclear Imagingmentioning
confidence: 96%
“…Second, increased LV 18 F-FDG uptake correlated with LVEF decline after two cycles and at the end of DOX therapy in a retrospective study including a cohort of 43 patients (130). Another interesting study explored 18 F-FDG myocardial uptake and myocardial perfusion (through 99m Tc-tetrofosmin SPECT) in a retrospective cohort of 332 patients followed for malignant disorders (131). As part of an oncologic PET protocol, patients were fasted to avoid myocardial 18 F-FDG uptake: 36% of patients had no 18 F-FDG uptake, 22.5% had diffuse 18 F-FDG uptake, 8% had focal 18 F-FDG uptake, and 30.5% had a focal uptake overlying the diffuse pattern 18 F-FDG uptake.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…Haider et al observed focal myocardial FDG uptake (not limited to the apex) in patients with myocardial abnormalities such as abnormal perfusion, impaired LV ejection fraction (LVEF), myocardial ischemia, and scarring. In addition, focal myocardial FDG uptake has been identified as a strong predictor of abnormal myocardial function/perfusion and as an independent predictor of ongoing ischemia and myocardial scarring [67]. Increased FDG uptake can persist for 48 h after stressinduced myocardial ischemia in stable coronary artery disease [68,69].…”
Section: Focal Fdg Uptake In the Left Ventricular Apexmentioning
confidence: 99%